If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5m + 4m = 27m Combine like terms: 5m + 4m = 9m 9m = 27m Solving 9m = 27m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-27m' to each side of the equation. 9m + -27m = 27m + -27m Combine like terms: 9m + -27m = -18m -18m = 27m + -27m Combine like terms: 27m + -27m = 0 -18m = 0 Divide each side by '-18'. m = 0 Simplifying m = 0
| 5y^2+7y-34=0 | | (7x-1)/5=x | | x^2-x/2-(x-4)^2/3≥0 | | 85=6k+5-(k+5) | | 85=6k+4-(k+5) | | 85=6k+4+(k+5) | | a-11=22 | | 85=6k+3-(2k+5) | | YGAF-YGAF= | | 6|4y-3|-2=16 | | 85=6k+3-(k+5) | | 84=6k+3-(k+2) | | df+2=2f-2d | | 84=6k+3-(k+5) | | 5y+3x-(-2y+2)= | | 625a+b+c=0.5 | | 84=7k+3-(k+5) | | 33+6y=141 | | -3(3+4b)+7=82 | | 625a+25b+c=0.5 | | 8x+5-3x+8=90 | | 4|5y-4|-1=7 | | -3(3+4b)7=82 | | y+6=1.33(x+3) | | 5-3[2x-7(3x-4)]= | | v+4=2v+6 | | Ax+px=w | | y+6=.75(x+3) | | UO+2=2UO | | y-6=-.75(x-3) | | ok+1=145 | | 2ab+6ac-2ya= |